Evangelicalism's Identity Crisis : The Meaning and Application of qōdesh and hágios for Christian Holiness and Distinctiveness in a Post-Christian South Africa - Christian, A.; Soal, A. (Vox Evangelica, 2022)
South African evangelicals find themselves in the midst of an identity crisis. The lives of many of them are marked by a pervasive worldliness which has resulted in a lack of holiness and a failure to be distinctively different from the surrounding culture and its practices. To address this problem, we explore the meanings of the terms qōdeš in Lev 11:1-47 and hagios in 1 John 2:15-17. These passages of Scripture suggest that holiness and spiritual distinctiveness demand radical obedience to God's Word, that will result in a marked separation from all forms of worldliness, including desires, attitudes, and behaviors. [Abstracted by: Fred W. Guyette] Abstract Number: OTA46-2023-OCT-2416
free
Keywords: Biblical Theology